Contrasting patterns of differentiation among three taxa of the rapidly diversifying orchid genus Ophrys sect. Insectifera (Orchidaceae) where their ranges overlap - Salvado, Pascaline; Gibert, Anaïs; Schatz, Bertrand; Vandenabeele, Lucas; Buscail, Roselyne; Vilasís, David; Feldmann, Philippe; Bertrand, Joris A M (Botanical journal of the Linnean Society, 2025)
In rapidly diversifying groups, taxa defined on the basis of typological criteria can be difficult to support with genetic data. The diversity observed in the insect-mimicking orchid genus Ophrys perfectly illustrates this situation; among 400 described species only 9–10 lineages are detectable by genetic markers such as nrITS. The three taxa described in the Ophrys insectifera group, O. insectifera, O. subinsectifera, and O. aymoninii, can be clearly distinguished by their flowers, which have evolved different phenotypes as a result of adaptation to specific pollinator insect species from three different families. However, genetic differentiation between these three taxa has never been really supported by population genetic data and their taxonomic status is still debated. Using population genomic approaches, we found a clustering consistent with the existence of three genetic entities where the geographic distributions of the three taxa overlap. Two of these clusters correspond to France populations of the widespread O. insectifera and the micro-endemic O. aymoninii. However, the last cluster grouped together all the Iberian individuals, suggesting that individuals phenotypically identified as either O. insectifera or O. subinsectifera are genetically weakly differentiated there. Populations of the two pairs of taxa thus may have experienced different patterns of inter-specific gene flow.